Iconography of the Frontispieces in the Costumbrist Collections of Social Types in Europe and Latin America - Cuvardic García, Dorde (2014)
In this article an iconographic analysis of frontispieces of the most important costumbrist collections of social types from Europe and Latin America is carried out. With a metaphoric intention, optical entertainment devices (magic lantern and tutilimundi) from the XIX century visual culture, along with objects related to their display (such as the magic lantern canvass where images are projected) are considered. ‘El diablo cojuelo’ (‘The crippled devil’), a satirical symbol, and the audience are also incorporated in this early frontispiece modes. This iconography used in costumbrist collections, as well as optical shows, offer to the audience a gallery of representative national social types. Moreover, in other frontispieces the analogy of costumbrist collections has also been identified with the significant practices of painting, drawing, and caricature. Finally, advertisement posters observed by an audience also represent another typical iconographic situation of costumbrist frontispieces. Resorting to analogies, the publishing projects of social types collections use for its representation verbal as well as visual practices.